2013
DOI: 10.1080/13854046.2012.750686
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Back Pain Treatment Outcomes Among Workers’ Compensation Patients: Important Information for Clinical Neuropsychologists

Abstract: Low back pain is an increasingly prevalent and costly issue in the United States. It is a particularly relevant problem for Workers' Compensation patients, who typically experience worse surgical and functional outcomes than their non-compensated counterparts. Neuropsychologists often provide intervention and assessment services to compensated patients with back pain, and thus it is critical they possess a basic understanding of the factors that might predispose an injured worker to poor spine surgery outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Because relatively few studies exist examining risk factors for poor lumbar fusion outcomes among the WC population, 4-5 , 8 , 12 we wanted to examine how psychosocial factors, chiefl y depression, impact lumbar fusion outcomes in a WC setting. WC patients tend to have worse lumbar fusion outcomes and lower postoperative RTW rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Because relatively few studies exist examining risk factors for poor lumbar fusion outcomes among the WC population, 4-5 , 8 , 12 we wanted to examine how psychosocial factors, chiefl y depression, impact lumbar fusion outcomes in a WC setting. WC patients tend to have worse lumbar fusion outcomes and lower postoperative RTW rates.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] A 2010 case-control study reported that WC subjects, when compared with the general population, had signifi cantly less improvement in mean Oswestry Disability Index and 36-Item Short Form Health Survey scores after fusion. [1][2][3][4][5][6][7] A 2010 case-control study reported that WC subjects, when compared with the general population, had signifi cantly less improvement in mean Oswestry Disability Index and 36-Item Short Form Health Survey scores after fusion.…”
mentioning
confidence: 99%
“…A recent summary of the CPGs and payer policies for LSF suggests that the spine care community needs to develop (or update) guidelines for candidacy using a biopsychosocial perspective, which should be collaborative across specialty/society groups. A biopsychosocial perspective is commonly used to evaluate a patient's risk of poor recovery from either conservative or surgical care for LBP (Wheeler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…First, the clinical tests and measures associated with fusion do not predict who is likely to benefit [38]. Second, it is well known that non-physical, non-pathoanatomical variables (e.g., depression) can independently influence outcomes after LSF [37]. Third, there is a notable lack of uniformity across clinical practice guidelines with respect to suggesting appropriate candidates for LSF [6,30].…”
Section: Introductionmentioning
confidence: 99%